Transition-state, branch-point associated cells give rise to the majority of ciliated cells in the mouse lung - Khalooghi, Keynoosh; Justus Liebig University Giessen (My University, 2022)
The lung is constantly receiving environmental insults from pathogens in inhaled air, necessitating permanent repair processes. To acquire and maintain regional functionalities of the lung, several different cell types are needed. In the intralobar bronchioalveolar airways and at branch points, a subpopulation of Club cells exists, known as variant Club cell (vClub), which express secretoglobin (Scgb1a1) but not cytochrome P450 (Cyp2f2). This subset is resistant to naphthalene and initiates repopulation of the airway at branch points in the vicinity of neuroepithelial bodies (NEBs). Due to the paucity of a unique molecular marker for vClub cells, the physiological role of these cells during both homeostasis and injury is poorly understood. To identify a specific marker gene for vClub cells, 2000 individual Club cells were analyzed, which were isolated by Fluorescence activated cell sorting (FACS) from CCSPmCherry SPCYFP reporter knock-in mouse strains. Single cell RNA sequencing analysis identified a small subpopulation of Club cells defined by co-expression of CCSP and Foxj1, which showed hallmarks of vClub cells such as localization at branch points and resistance to naphthalene injury. Subsequent lineage tracing demonstrated that CCSP+ Foxj1+ cells give rise to almost 60% of all ciliated cells. Diphtheria toxin (DTA) mediated ablation of CCSP+ Foxj1+ cells reduced cellularity of the bronchiolar epithelium, causing a reduction in the number of ciliated cells and an even more substantial depletion of regular Club cells. The results indicate a high cellular plasticity of the airway epithelium during regeneration, allowing regular club cells to compensate for the absence of CCSP+ Foxj1+ cells. However, enforcement of ciliated cell formation by regular club cells comes with a price, resulting in exhaustion of club cells, which demonstrates some limitations of compensatory lung regeneration mechanisms.
Keywords: ddc:570